Magnetic reversal and pinning in a perpendicular zero-moment half-metal - Venkatesan, Munuswamy; Coey, John; Stamenov, Plamen; Rode, Karsten; Atcheson, Gwenael (My University, 2021)
Compensated ferrimagnets are promising materials for fast spintronic applications based on domain-wall motion as they combine the favorable properties of ferromagnets and antiferromagnets. They inherit from antiferromagnets immunity to external fields, fast spin dynamics, and rapid domain-wall motion. From ferromagnets they inherit straightforward ways to read out the magnetic state, especially in compensated half metals, where electrons flow in only one spin channel. Here, we investigate domain structure in compensated half-metallic Mn2Ru0.5Ga films and assess their potential in domain-wall motion-based spin-electronic devices. Our focus is on understanding and reducing domain-wall pinning in unpatterned epitaxial thin films. Two modes of magnetic reversal, driven by nucleation or domain-wall motion, are identified for different thin film deposition temperatures (Tdep). The magnetic aftereffect is analyzed to extract activation volumes (V∗), activation energies (EA), and their variation (ΔEA). The latter is decisive for the magnetic reversal regime, where domain-wall motion dominated reversal (weak pinning) is found for ΔEA<0.2eV and nucleation dominated reversal (strong pinning) for ΔEA>0.5eV. A minimum ΔEA=28meV is found for Tdep=290∘C. Prominent pinning sites are visualized by analyzing virgin domain patterns after thermal demagnetization. In the sample investigated they have spacings of order 300 nm, which gives an upper limit of the track width of spin-torque domain-wall motion-based devices.
PUBLISHED
Keywords: Demagnetization; Domain walls; Domains; Ferrimagnetism; Magnetization dynamics; Nanoscience & Materials; FABRICATION; NANOSTRUCTURES; Nanotechnology; Physics